Polysaccharide-containing solid oral compositions

JP7652406B2Active Publication Date: 2025-03-27BIZEN CHEM
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020165008
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-30
Publication Date
2025-03-27
Estimated Expiration
2040-09-30

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、腸内徐放性を有する、腸溶性固形経口組成物を提供できる。また、本発明によれば、腸内徐放性成分としてのサイリウムの使用方法を提供できる。本発明によれば、腸内において有効成分を徐放できるため、有効成分が短時間で大量に吸収されることを抑制できる。本発明によればセルロース誘導体、キサンタンガム、ヒアルロン酸、カラギーナン、ペクチン、タラガム、及びプルランからなる群から選択される少なくとも1種の多糖類及びサイリウムを含有する固形組成物の硬度を高めることができる。本発明によればビタミンの体内利用率を高めることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652406000006
    Figure 0007652406000006
  • Figure 0007652406000007
    Figure 0007652406000007
  • Figure 0007652406000008
    Figure 0007652406000008
Patent Text Reader

Abstract

To provide an enteric-coated solid oral composition that can be produced more conveniently and can be sustainedly released in the intestines.SOLUTION: A solid oral composition has a core part containing at least one polysaccharide selected from the group consisting of cellulose derivative, psyllium, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan, the core part being coated with an enteric coating agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to solid oral compositions containing polysaccharides and methods of using psyllium. [Background technology]

[0002] Functional foods for nutritional improvement or nutritional supplementation are commercially available as solid supplements, etc. On the other hand, enteric preparations are known in which a core agent containing an active ingredient such as a functional ingredient or a medicinal ingredient is coated with an enteric coating agent to deliver the active ingredient to the intestine. In this preparation, the enteric coating does not dissolve in the stomach but dissolves in the intestine, so that the core agent is inhibited from disintegrating under the influence of gastric juice, and the active ingredient is released by disintegrating in the intestine.

[0003] Furthermore, attempts have been made to slow-release the core agent delivered to the intestine by enteric coating. Patent Document 1 describes an enteric preparation having a structure in which at least three enteric layers, each consisting of a portion containing an active ingredient and an enteric coating coating the portion, are superimposed, and a gastric layer is provided on the outside, which enables the active ingredient to be delivered to the small intestine and then gradually released in the small intestine without being released in the stomach even when taken orally. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-119642 A Summary of the Invention [Problem to be solved by the invention]

[0005] The enteric preparation described in Patent Document 1 has a complicated manufacturing process due to the formation of at least three enteric layers. The object is to provide an enteric solid oral composition that can be produced more simply and has sustained release properties in the intestine. The object is to provide a new use of psyllium. The object is to provide a vitamin absorption enhancer. [Means for solving the problem]

[0006] The present inventors have found that, in a solid oral composition having a core coated with an enteric coating agent, by blending at least one polysaccharide selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan in the core, a solid oral composition having intestinal sustained release properties and enteric properties or a vitamin absorption enhancer having high bioavailability of vitamins can be obtained. The present inventors have also found that psyllium increases the hardness of the core containing polysaccharides (preferably further containing an excipient).

[0007] The present invention encompasses, for example, the following subject matter: Section 1. A solid oral composition having a core containing at least one polysaccharide selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan, the core being coated with an enteric coating agent. Section 2. Item 2. The composition according to item 1, wherein the polysaccharide is at least one selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, and carrageenan. Section 3. Item 3. The composition according to item 1 or 2, wherein the polysaccharide is psyllium. Section 4. Item 2. The composition according to item 1, wherein the core contains at least one polysaccharide selected from the group consisting of cellulose derivatives, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan, and psyllium. Section 5. Item 5. The composition according to item 4, wherein the core contains at least one polysaccharide selected from the group consisting of cellulose derivatives, xanthan gum, hyaluronic acid, and carrageenan, and psyllium. Section 6. Item 5. The composition according to item 4, wherein the core contains HPMC and psyllium. Section 7. 7. The composition according to any one of items 1 to 6, wherein the polysaccharide is contained in an amount of 1 to 90% by mass based on the total mass of the core. Section 8. 7. The composition according to any one of items 1 to 6, comprising psyllium in an amount of 0.4 to 30% by mass based on the total mass of the core. Section 9. 9. The composition according to any one of items 1 to 8, wherein the polysaccharide has an average particle size of 1 μm to 400 μm. Section 10. Item 10. The composition according to any one of Items 1 to 9, wherein the enteric coating agent comprises at least one selected from the group consisting of shellac, zein, and sodium alginate. Section 11. 11. The composition according to any one of Items 1 to 10, which is an intestinal sustained release preparation. Section 12. Item 12. The composition according to any one of Items 1 to 11, which is intended for delivery to at least one site selected from the group consisting of the jejunum, the ileum, and the large intestine. Section 13. Item 13. The composition according to any one of Items 1 to 12, which is for food use. Section 14. Item 14. The composition according to any one of Items 1 to 13, wherein the core further contains a vitamin and is for improving vitamin absorption. Section 15. In the enteric solid oral composition, the core is coated with an enteric coating agent, The composition is characterized in that psyllium is blended into the core to impart a sustained release function in the intestines to the composition. How to use psyllium. Section 16. Item 16. The method according to item 15, wherein the amount of psyllium blended is 0.4 to 70% by mass based on the total mass of the core. Section 17. Item 17. The method according to item 15 or 16, wherein the average particle size of the psyllium is 1 μm to 400 μm. Section 18. Item 18. The method according to any one of Items 15 to 17, wherein the enteric coating agent is at least one selected from the group consisting of shellac, zein, and sodium alginate. Section 19. A method for improving the hardness of a solid composition containing at least one polysaccharide selected from the group consisting of cellulose derivatives, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan, by blending the psyllium with the at least one polysaccharide.

[0008] The invention may include the following subject matter. Section A. In the enteric solid oral composition, the core is coated with an enteric coating agent, The composition is characterized in that at least one polysaccharide selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan is blended in the core, thereby imparting a sustained release function in the intestine to the composition. A method of using said polysaccharides. Effect of the Invention

[0009] According to the present invention, an enteric solid oral composition having intestinal sustained release properties can be provided. Also, according to the present invention, a method for using psyllium as an intestinal sustained release component can be provided. According to the present invention, since the active ingredient can be sustainedly released in the intestine, it is possible to suppress the active ingredient from being absorbed in large amounts in a short period of time. According to the present invention, it is possible to increase the hardness of a solid composition containing psyllium and at least one polysaccharide selected from the group consisting of cellulose derivatives, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan. According to the present invention, it is possible to increase the utilization rate of vitamins in the body. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a graph in which the dissolution rate (%) is plotted on the vertical axis and the time elapsed since being placed in the second liquid is plotted on the horizontal axis, with the dissolution rate at each predetermined time being plotted, and is used to derive the 50% dissolution time. [Diagram 2]FIG. 2 is a graph showing the dissolution rates of uncoated tablets 4-3 (■) containing polysaccharides and uncoated tablets 4-4 (●) not containing polysaccharides (Test Example 4 (4-5)). [Diagram 3] FIG. 3 is a graph showing the dissolution rate of coated tablet 4-3 (Test Example 4 (4-6)). [Figure 4] Figure 4 shows X-ray images of subjects A and B who took plain tablet 4-2 (Test Example 5). From the left, the images are taken 30 minutes, 90 minutes, and 180 minutes after taking the tablet. The white parts in the images are the solid oral composition taken. [Diagram 5] Figure 5 shows X-ray images of subjects C and D who took coated tablet 4-1 (Test Example 5). From the left, for C, the images are taken 30 minutes, 90 minutes, 180 minutes, and 240 minutes after taking the tablet, and for D, the images are taken 180 minutes, 240 minutes, 300 minutes, and 360 minutes after taking the tablet. The white parts in the images are the solid oral composition that was taken. [Figure 6] FIG. 6 is a graph showing the in vivo utilization rate of vitamin C contained in the coated tablets (6-1) to (6-4) (Test Example 6). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention is an oral solid composition having a core coated with an enteric coating agent, the core containing at least one polysaccharide selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan. Another invention is a method for using psyllium in an oral solid composition having an enteric core coated with an enteric coating agent, the method being characterized in that psyllium is blended into the core to impart a sustained release function in the intestine to the composition.

[0012] The solid oral composition has a core coated with an enteric coating agent. The core is not particularly limited as long as it disintegrates in the intestine, and is, for example, a plain tablet. The core contains at least one polysaccharide selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan. By containing the polysaccharide, the core can be gradually disintegrated in the intestine without immediately disintegrating. Therefore, these polysaccharides act as an intestinal sustained release component that imparts a sustained release function to the core.

[0013] The polysaccharide acting as a sustained release component can be at least one selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, carrageenan, pectin, and pullulan, and is preferably at least one selected from the group consisting of cellulose derivatives, psyllium, xanthan gum, hyaluronic acid, and carrageenan, and from the viewpoint of natural origin, is more preferably at least one selected from the group consisting of psyllium, xanthan gum, hyaluronic acid, and carrageenan, and is even more preferably at least one selected from the group consisting of psyllium, xanthan gum, and hyaluronic acid, and is even more preferably at least one selected from the group consisting of psyllium and xanthan gum, and is particularly preferably psyllium.In addition, the polysaccharide can also be at least one selected from the group consisting of psyllium, xanthan gum, and carrageenan.

[0014] Examples of cellulose derivatives include hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), methylcellulose, ethyl cellulose, and carboxymethylcellulose (CMC), and these can be used alone or in combination of two or more. Preferred are hydroxypropyl methylcellulose and hydroxypropyl cellulose (HPC), and more preferred is hydroxypropyl methylcellulose. The cellulose derivative does not include cellulose.

[0015] The psyllium is preferably a pulverized product of the seed husk obtained from the seeds of Plantago ovata, a plant of the family Plantaginaceae. Such a pulverized product may be refined. Examples of such a pulverized product include psyllium seed husk powder, psyllium seed gum, and isagol, and one or more of them may be used alone or in combination. The more preferred psyllium is psyllium seed gum.

[0016] The average particle size (D50) of the polysaccharide is, for example, 1 μm to 400 μm, preferably 1 μm to 200 μm, and more preferably 1 μm to 100 μm. When the average particle size is within this range, the core has the hardness required for production, and is advantageous in that it has a longer sustained release property in the intestine. The average particle size (D50) is determined by a laser diffraction / scattering method.

[0017] The content of the polysaccharide in the core may be appropriately determined depending on the delivery site, the type of active ingredient, etc. For example, it may be 1 to 90% by mass, preferably 5 to 60% by mass, and more preferably 10 to 60% by mass, based on the total mass of the core. When the content of the polysaccharide in the core is within this range, it is advantageous in that the core has a hardness required for production and has a longer sustained release in the intestine. In the case of psyllium, the content may be, for example, 1 to 90% by mass, 1 to 70% by mass, 1 to 60% by mass, 5 to 60% by mass, 10 to 60% by mass, etc., based on the total mass of the core, preferably 3 to 40% by mass, and more preferably 3 to 30% by mass.

[0018] The core can be made into a solid form such as tablets, pills, powders, granules, etc. by adding appropriate amounts of active ingredients, excipients, binders, disintegrants, moisturizers, lubricants, colorants, flavorings, etc. to the polysaccharides in a conventional manner. Examples of the solid form include excipients such as lactose, sucrose, sodium chloride, glucose, urea, starch, calcium carbonate, kaolin, crystalline cellulose, etc., binders such as water, ethanol, propanol, simple syrup, glucose solution, starch solution, gelatin solution, methylcellulose, potassium phosphate, polyvinylpyrrolidone, etc., disintegrants such as sodium alginate, dry starch, agar powder, laminaran powder, calcium carbonate, sodium bicarbonate, polyoxyethylene sorbitan fatty acid ester, sodium lauryl sulfate, stearic acid monoglyceride, etc., moisturizers such as glycerin, adsorbents such as kaolin, bentonite, colloidal silicic acid, etc., and lubricants such as purified talc, stearates, boric acid powder, polyethylene glycol, etc.

[0019] The content of the excipient in the core may be appropriately determined depending on the dosage form, size of the composition, etc. For example, it may be 30 to 95% by mass, etc., relative to the total mass of the core. The content of other components in the core may be appropriately determined depending on the dosage form, sustained release properties, size of the composition, etc. For example, it may be 0.1 to 20% by mass, 0.3 to 10% by mass, etc.

[0020] The active ingredient is not particularly limited as long as it is required to be supplied to the intestine. The active ingredient may be a medicinal ingredient used in pharmaceuticals, a functional ingredient used in functional foods and health foods, etc. Examples of the active ingredient required to be supplied to the small intestine (jejunum and ileum) include nutritional ingredients and functional ingredients such as glucose, garlic, royal jelly, vitamins (preferably water-soluble vitamins, more preferably vitamin C), lactoferrin, enzymes, GABA (γ-aminobutyric acid), glycine, and theanine. Examples of the active ingredient required to be supplied to the ileum include intestinal immune ingredients such as lactic acid bacteria (dead bacteria, live bacteria), short-chain fatty acids, bifidobacteria, collagen, β-glucan, and pollen. Examples of the active ingredient required to be supplied to the large intestine include monosaccharides, amino acids, minerals, isoflavones, lactic acid bacteria (live bacteria), and intestinal bacteria activating ingredients such as bifidobacteria.

[0021] The content of the active ingredient in the core may be appropriately selected depending on the number of administrations, administration intervals, administration period, administration target, etc. For example, it can be 1 to 95% by mass, 5 to 80% by mass, etc., preferably 10 to 70% by mass, and more preferably 10 to 65% by mass, relative to the total mass of the core.

[0022] The core can be appropriately manufactured using a formulation technique known to those skilled in the art. For example, granules can be manufactured by wet granulation or dry granulation. For example, tablets can be manufactured by compressing granules manufactured by wet granulation or dry granulation.

[0023] The core may be formed by uniformly mixing the various components. Alternatively, the core may be formed by forming a core with the active ingredient and any optional ingredient as necessary, and coating the core with the polysaccharide and any optional ingredient as necessary, in order to delay the release of the active ingredient. In this way, the components constituting the core may be mixed homogeneously or non-homogeneously in any order, and then molded. However, an embodiment in which all of the polysaccharide is blended in the core and the core is coated with the active ingredient to form the core is not preferred, since it is difficult to obtain the effect of delaying the release of the active ingredient by the polysaccharide.

[0024] The form of the core is preferably a tablet, pill, granule or powder, more preferably a tablet, pill or granule, and particularly preferably a tablet or pill from the viewpoint of control of disintegration.

[0025] When the core contains polysaccharides, the hardness of the molded product (tablet) obtained by tableting the core is lower than that of a core not containing polysaccharides (which usually contains a larger amount of excipients). Here, when psyllium is blended into the core containing other polysaccharides, the hardness is improved compared to when psyllium is not blended. From the viewpoint of improving the core hardness, it is preferable that the core contains at least psyllium. The blending amount of psyllium can be 1 to 100 mass%, 3 to 100 mass%, 5 to 100 mass%, etc., based on the total mass of the polysaccharides contained in the core, and is preferably 10 to 100 mass%, more preferably 25 to 100 mass%, and particularly preferably 50 to 100 mass%.

[0026] The specific surface area of ​​psyllium is 0.01 m 3 / g~100m 3 / g, 0.05m 3 / g~100m 3 / g, etc., and 0.1m 3 / g~100m 3 From the viewpoint of improving hardness, it is preferable that the hardness is 0.5m / g. 3 / g~100m 3 / g, and particularly preferably 1.0m 3 / g~100m 3 / g.

[0027] The average particle size (D50) of psyllium can be 1 μm to 400 μm, 1 μm to 200 μm, etc., and is preferably 1 μm to 150 μm from the viewpoint of improving hardness. It is more preferably 1 μm to 70 μm, and particularly preferably 1 μm to 50 μm. The average particle size (D50) is determined by a laser diffraction / scattering method.

[0028] The core is provided with enteric properties by being coated with an enteric coating agent. The enteric coating agent is not particularly limited as long as it is capable of suppressing the disintegration of the core without dissolving or decomposing in the stomach, but naturally derived substances are preferred. Examples of the enteric coating agent include shellac, zein, sodium alginate, etc., and one type may be used alone or two or more types may be used in combination. The enteric coating agent is preferably at least one selected from the group consisting of shellac and zein, and more preferably shellac or zein.

[0029] When coating the core with an enteric coating agent, a pharma- ceutical or food-acceptable plasticizer may be added to the enteric coating agent. Coating can be appropriately performed using techniques known to those skilled in the art. For example, the coating can be performed by uniformly spraying a suspension containing an enteric coating agent, a plasticizer, etc. onto the core (e.g., plain tablet) in an appropriate device, such as a coating pan, a coating granulator, or a fluidized bed device, and drying the suspension. The coating layer formed by coating is preferably a single layer, but may be two or three layers. The thickness of the coating layer is not particularly limited as long as it can protect the core in the stomach, and can be, for example, 1 μm to 3 μm.

[0030] The content of the enteric coating agent in the solid oral composition is, for example, 3 to 15 mass %, preferably 5 to 10 mass %, and more preferably 7 to 8 mass %, relative to the total mass of the solid oral composition. The solid oral composition preferably has one coating layer of an enteric coating agent.

[0031] The solid oral composition has intestinal sustained release properties by containing the polysaccharide in the core. The sustained release properties are determined based on the results of a dye (Red No. 40) dissolution test described in the Examples. The 50% dissolution time is the time from the introduction of the second liquid until 50% of the dye is dissolved. If the 50% dissolution time of a solid oral composition containing a polysaccharide in the core is 108% or more of the 50% dissolution time of a control containing no polysaccharide, the polysaccharide is determined to be capable of imparting intestinal sustained release properties. The sustained release properties can be such that the 50% dissolution time is, for example, 110% or more, 120% or more, 130% or more, 140% or more, 150% or more, 160% or more, 170% or more, 180% or more, 190% or more, 200% or more, 250% or more, 300% or more, 350% or more, etc., of that of the control, with 130% or more being preferred, 170% or more being more preferred, 200% or more being even more preferred, and 250% or more being particularly preferred.

[0032] By incorporating an active ingredient in the core, the active ingredient can be delivered to at least one intestinal site selected from the group consisting of the jejunum, ileum, and large intestine, in some cases. Preferred delivery sites are (1) only the jejunum and (2) the intestinal site excluding the jejunum and large intestine from the at least one intestinal site selected from the group consisting of the jejunum, ileum, and large intestine, and more preferred delivery sites are the ileum, large intestine, the jejunum and ileum, the jejunum, ileum, and large intestine, or the ileum and large intestine.

[0033] The delivery site can be determined based on the results of a dye (Red No. 40) dissolution test described in the Examples. If the dye dissolution rate (first dissolution amount) is 25% or more during the 2-hour period (period assumed to be the jejunum residence time) after the second liquid is added, it can be considered that the dye can be delivered to the jejunum. If the dye dissolution rate (second dissolution amount) is 25% or more during the 2- to 5-hour period (period assumed to be the ileum residence time) after the second liquid is added, it can be considered that the dye can be delivered to the ileum. If the dye dissolution rate (third dissolution amount) is 25% or more during the 5- to 24-hour period (period assumed to be the large intestine residence time) after the second liquid is added, it can be considered that the dye can be delivered to the large intestine.

[0034] The second elution amount does not include the first elution amount, and the third elution amount does not include the first elution amount and the second elution amount.

[0035] For example, if the pigment dissolution rate 2 hours after the addition of the second liquid (first dissolution amount) is 30%, the pigment dissolution rate 5 hours after the addition of the second liquid (first dissolution amount + second dissolution amount) is 60%, and the pigment dissolution rate 24 hours after the addition of the second liquid (first dissolution amount + second dissolution amount + third dissolution amount) is 100%, then the first dissolution amount, second dissolution amount, and third dissolution amount are 30%, 30%, and 40%, respectively, and therefore the composition can be considered to be capable of being delivered to the jejunum, ileum, and large intestine, and can be determined to be a solid oral composition for delivery to the jejunum, ileum, and large intestine.

[0036] Furthermore, for example, if the pigment dissolution rate 2 hours after the addition of the second liquid (first dissolution amount) is 10%, the pigment dissolution rate 5 hours after the addition of the second liquid (first dissolution amount + second dissolution amount) is 60%, and the pigment dissolution rate 24 hours after the addition of the second liquid (first dissolution amount + second dissolution amount + third dissolution amount) is 100%, then the first dissolution amount, second dissolution amount, and third dissolution amount are 10%, 50%, and 40%, respectively, and therefore the composition can be regarded as capable of being delivered to the ileum and large intestine, and can be determined to be a solid oral composition for delivery to the ileum and large intestine.

[0037] The degree of sustained release or the delivery site can be adjusted by the type of polysaccharide, the blending ratio of the polysaccharide, the particle size of the polysaccharide, etc. The sustained release property can be enhanced and the disintegration delay effect can be obtained by using a polysaccharide having a strong sustained release property (release delay effect) among the polysaccharides, increasing the blending ratio of the polysaccharide, reducing the particle size of the polysaccharide, etc.

[0038] The solid oral composition of the present invention can be used as a food composition or a pharmaceutical composition, and is preferably used as a food composition. As the food composition, a supplement is preferable.

[0039] In the method for using psyllium of the present invention, an enteric solid oral composition having a core coated with an enteric coating agent is provided with psyllium in the core, thereby imparting a sustained release function in the intestine to the composition. Surprisingly, by being incorporated into the core, psyllium can delay the disintegration of the enteric solid oral composition in the intestine, i.e., impart a sustained release function to the composition. Other matters in the method for using psyllium of the present invention are the same as those described in the explanation of the solid oral composition of the present invention.

[0040] In the method for improving the hardness of a solid composition of the present invention, psyllium is blended with at least one polysaccharide selected from the group consisting of cellulose derivatives, xanthan gum, hyaluronic acid, carrageenan, pectin, tara gum, and pullulan, thereby improving the hardness of a solid composition (e.g., a tablet, a core of the solid oral composition, etc.) containing the at least one polysaccharide and psyllium.

[0041] The solid oral composition of the present invention can be used as a vitamin absorption enhancer by incorporating a vitamin into the core. When this agent is taken, the vitamin in the composition is hardly released in the stomach. Furthermore, since the composition does not disintegrate immediately after reaching the small intestine (jejunum), the vitamin is not released all at once in the jejunum. Since the composition disintegrates gradually in the small intestine and releases the vitamin gradually, the vitamin is gradually absorbed over a long period of time, and as a result, the utilization rate of the vitamin in the body is improved. This is the same even if the vitamin is replaced with another active ingredient. EXAMPLES

[0042] Hereinafter, one embodiment of the present invention will be described in more detail with reference to test examples, but the present invention is not limited thereto. The materials, devices, etc. used in the following examples are as follows. Color: Food coloring No. 40; San-Ei Gen FFI Co., Ltd. Maltose: Sanmalt S; Hayashibara Publishing Calcium stearate: Calcium stearate; Qingdao Omiya Foods Co., Ltd. Hydroxypropyl methylcellulose (HPMC): NE4000; Shin-Etsu Chemical Co., Ltd.; average particle size 68 μm Xanthan gum: Bistop D-3000; San-Ei Gen FFI; average particle size 94 μm Psyllium: Foodmade P-100; Shikibo Co.; average particle size 100 μm Psyllium powder: Foodmade P-100 made into small particles; Shikibo Co.; average particle size 14 μm Hyaluronic acid: Hyaluronic acid Rv; Nippon Shinyaku Co., Ltd.; average particle size 77 μm Carrageenan: SATIAGUM MM30; Unitech Foods; average particle size 49 μm Pectin: UNIPECTINE AYD509ME; Unitech Foods; average particle size 105 μm Tara gum: VIDogum SP175; Unitech Foods; average particle size 124 μm Pullulan: Food additive pullulan; Hayashibara; average particle size 338μm Cellulose: SOYAFIBE S-DA100; Fuji Oil Co.; average particle size 30 μm Gum arabic: Gum arabic; Nippon Powder Pharmaceuticals; average particle size 81 μm Guar gum: Guapack PF-20 (DSP Gokyo Food & Chemical Co., Ltd.; average particle size 61 μm) Sieve: Standard sieve; Iida Seisakusho; mesh size 710 μm Punches and dies: Two Nine Japan Co., Ltd.; diameter 9.0 mm Tablet press: CLE / ANPRESS Correct 19K; Kikusui Seisakusho Co., Ltd. Water-based shellac liquid: AQshelax; Freund Corporation Sucrose fatty acid ester: Ryoto Sugar Ester S-570; Mitsubishi Chemical Foods Corporation D-Sorbitol: Sorbitol T-70; Mitsubishi Corporation Foodtech Co., Ltd. Coating machine: DRIACOATER; Powrex Hardness tester: HARDNESS TESTER; FUJIWARA Dissolution tester: NTR-3000; Toyama Sangyosha Absorption photometer: U-2900; HITACHI Dissolution test 1st fluid: 2.0 g of sodium chloride dissolved in 7.0 mL of hydrochloric acid and water to make 1000 mL (pH 1.2) Dissolution test second fluid: 1 volume of phosphate buffer solution (pH 6.8) plus 1 volume of water

[0043] Production Example 1: Production of polysaccharide-containing enteric composition Tablets (plain tablets) of about 400 mg (396 mg to 406 mg) containing the polysaccharides shown in Table 1 were prepared, and enteric-coated with shellac to produce enteric solid oral compositions. The details are as follows.

[0044] 150g of polysaccharide powder, 52.5g of pigment, and 1252.5g of maltose were placed in a plastic bag, then the plastic bag was inflated with air, the mouth was tied by hand, and the plastic bag was mixed by hand for 1 minute mainly in an up-down direction. The mixture was sieved through a sieve to obtain a sieve-passed powder (first mixed powder). 90g of the first mixed powder was taken, and this powder and 45g of calcium stearate were placed in a plastic bag, the plastic bag was inflated with air, the mouth was tied by hand, and the plastic bag was mixed by hand for 3 seconds mainly in an up-down direction, and then sieved through a sieve to obtain a sieve-passed powder. This powder was placed in a plastic bag, the plastic bag was inflated with air, the mouth was tied by hand, and the plastic bag was mixed by hand for 3 seconds mainly in an up-down direction to obtain a second mixed powder. The second mixed powder and the remaining first mixed powder were placed in a plastic bag, the bag was inflated with air, the opening was tied by hand, and the bag was shaken by hand mainly vertically for 10 seconds to mix, obtaining 1500 g of raw powder for use as the raw material for uncoated tablets. The polysaccharide blending ratio was 10% by mass.

[0045] When producing raw powder for uncoated tablets with a polysaccharide blending ratio of 5% by mass as shown in Table 1, the amount of polysaccharide powder used was changed from 150 g to 75 g, and the amount of maltose used was changed from 1252.5 g to 1327.5 g, and raw powder was obtained in the same manner. Using a tablet press equipped with a punch and die, the raw material powder was compressed under an environment of a main pressure setting of 1.9 to 2.1 and a preload setting of 3.5 to 5.0 to produce uncoated tablets (approximately 400 mg). The hardness of three uncoated tablets was measured with a hardness tester, and the average value is shown in Table 1. The weight per tablet is also shown in Table 1.

[0046] A mixture of 2000g of aqueous shellac solution and 40g of sucrose fatty acid ester was heated to 60°C to dissolve the ester, and then 40g of D-sorbitol was added and dissolved to prepare a coating solution. 1kg of plain tablets were fed into a coating machine, the inlet air temperature was set to 80°C, and the plain tablets were rotated. The coating solution was sprayed onto the rotating plain tablet surface to coat it. The amount of coating was 7.4% by mass based on the total mass of the solid oral composition.

[0047] Preparation Example 2: Preparation of an enteric composition not containing polysaccharides (control) An enteric composition (control) was obtained in the same manner as in Production Example, except that no polysaccharide was added.

[0048] Test Example 1: Measurement of 50% dissolution time The enteric coated tablets (test tablets) produced in Production Examples 1 and 2 were subjected to a dissolution test using a dissolution tester, and the sustained release property was tested by measuring the dissolution of the dye with an absorptiometer. Six test tablets each produced in Production Examples 1 and 2 were subjected to a dissolution tester, and a dissolution test was performed according to the dissolution test method (paddle method) described in the 17th edition of the Japanese Pharmacopoeia. One test tablet was placed in a container containing the first dissolution test liquid, and the liquid was stirred with a paddle. After one hour, the test tablet was removed from the liquid and placed in a container containing the second dissolution test liquid, and the liquid was stirred with a paddle. After the test tablet was placed in the second dissolution test liquid, 5 mL of the liquid was sampled at predetermined times (30 minutes, 60 minutes, 120 minutes, 300 minutes, 540 minutes, and 1440 minutes) and the absorbance (510 nm) was measured with an absorption photometer. The other five tablets were similarly tested.

[0049] In addition, after the prescribed time had elapsed, the condition of the test tablet was visually observed. If the tablet had completely disintegrated, it was deemed that the entire amount of dye had dissolved at that point, and the absorbance at that point was taken as the dissolution rate of 100%. The dissolution rate at each prescribed time point was calculated from the absorbance at the prescribed time point prior to that point. In addition, when visually observed, the test tablet was judged to have completely disintegrated when absolutely no test tablet residue was found in the container, or when any residue was found but was a soft substance that clearly did not retain its original shape.

[0050] A graph was created by plotting the dissolution rate (%) at each predetermined time on the vertical axis and the time elapsed since the tablet was placed in the second liquid on the horizontal axis, and the time elapsed when the dissolution rate reached 50% (50% dissolution time) was derived from the graph. As an example, graphs for the control (●), 10% xanthan gum test tablet (■), and 10% HPMC test tablet (◆) are shown in Figure 1. From this graph, it can be seen that the 50% dissolution time was 60 minutes for the control, 350 minutes for the 10% xanthan gum test tablet, and 420 minutes for the 10% HPMC test tablet. The 50% dissolution times of the 10% xanthan gum test tablet and the 10% HPMC test tablet were 583% (350 / 60) and 700% (420 / 60) of the control, respectively, confirming sufficient sustained release properties, and indicating that xanthan gum and HPMC are components that impart sustained release properties. In the same manner, the 50% dissolution times of the other test tablets were determined and are shown in Table 1.

[0051] [Table 1]

[0052] HPMC, xanthan gum, carrageenan, hyaluronic acid, psyllium (including psyllium fine powder), pectin, pullulan and tara gum have a 50% longer dissolution time than the control, demonstrating their sustained release properties. If the sustained release properties are strong, it is possible to achieve the desired sustained release time with a small amount of the compounded product. Furthermore, strong sustained release properties can be obtained by increasing the amount of these polysaccharides (sustained release ingredients) compounded. Test tablets containing HPMC, xanthan gum, carrageenan, hyaluronic acid, psyllium (including psyllium fine powder), pectin, pullulan or tara gum had a hardness of 3kgf / cm 2 From the above results, it was confirmed that the hardness was sufficient for practical use.

[0053] The graph shown in FIG. 1 was also used to determine the intestinal delivery site based on the amount of dye eluted (first elution amount, second elution amount, third elution amount). The dye elution ratios of the 10% by mass xanthan gum test tablet after 2 hours, 5 hours, and 24 hours were 14.7%, 42.6%, and 100%, respectively, so the first elution amount, second elution amount, and third elution amount were 14.7%, 27.9%, and 57.4%, respectively. As a result, it was found that this test tablet was delivered to the jejunum in a small amount, and could be used for ileal delivery and large intestine delivery, and is more suitable for large intestine delivery.

[0054] Test tablets containing cellulose, pectin, gum arabic or guar gum were determined to be suitable for jejunal delivery but not for ileal delivery. Test tablets containing HPMC, xanthan gum, carrageenan, hyaluronic acid, psyllium (including psyllium micropowder), pectin, pullulan, tara gum, cellulose, gum arabic or guar gum were suitable for jejunal delivery applications. Test tablets containing HPMC, xanthan gum, carrageenan, hyaluronic acid, psyllium (including psyllium micropowder), pullulan or tara gum were suitable for ileal delivery applications. Test tablets containing HPMC or xanthan gum were suitable for colonic delivery applications.

[0055] Test Example 2: Improvement of tablet hardness by adding psyllium The HPMC and psyllium were formulated in the amounts shown in Table 2, with 3.5% by mass of red No. 40 coloring, 3% by mass of calcium stearate, and the remainder as maltose, and were simply mixed to prepare powder for tableting. The psyllium used here was psyllium fine powder and Foodmade P-100, which have different particle sizes, and are referred to as psyllium A and psyllium B, respectively. A 9.5 mmφ two-stage R-type punch was attached to a rotary tablet press, and tablets were obtained from each powder with the main pressure scale set at 1.7, preload scale set at 3.0, and tablet weight set at 400 mg. The hardness of the obtained tablets was measured using a hardness tester, and the average value was used for evaluation (n=10).

[0056] Table 2 shows the tablet hardness obtained from each formulation. The sample containing no psyllium and containing 10% HPMC was used as the standard, and the difference in hardness was verified by calculating the rate of change in hardness. When psyllium A was added, an increase in hardness was observed as the blending ratio increased (3-2A to 3-7A). In addition, an increase in hardness was observed when only psyllium A was used compared to the standard sample using only HPMC, making it clear that psyllium A also functions as a binder to improve the moldability of the standard tablets (3-7A). The tablet hardness was also slightly improved when psyllium B was added. The hardness of HPMC tablets was improved by adding psyllium to HPMC.

[0057] [Table 2]

[0058] Similarly, the hardness of tablets produced by varying the total amount of polysaccharides from 3.0% to 30% and changing the ratio of HPMC to psyllium A was measured. The results are shown in Table 3. Normally, increasing the amount of polysaccharide reduces the hardness of the tablet, but it was confirmed that even when the amount of polysaccharide was high (i.e., 20% by mass and 30% by mass), the tablet had sufficient hardness as an enteric tablet.

[0059] [Table 3]

[0060] Test Example 3: Correlation analysis between the physical properties of psyllium and its effect on improving moldability The particle size distribution and specific surface area of ​​psyllium A and B were measured, and they were observed using an electron microscope. The measurement conditions for each were as follows:

[0061] <Average particle diameter (D50)> The measurement principle is a wet laser diffraction / scattering method. During the measurement, laser light is detected using the transmission method, the particle refractive index is 1.81, and the sample type is non-spherical particle, and the particle size distribution is measured. The cumulative 50% diameter (D50) is calculated based on the distribution and used as the average particle size. Measuring equipment: Microtrac MT3200II (Microtrac Bell Co., Ltd.) Measurement solvent: isopropanol (solvent refractive index is 1.38) Measurement time: 10 seconds

[0062] <Specific surface area> The sample powders used for the measurement were thoroughly dried in advance to remove excess moisture adhering to the powder surface, and then the specific surface area was measured. Using helium as the carrier gas and nitrogen as the gas to be adsorbed onto the particle surface, the specific surface area of ​​each was calculated based on the calculation principle based on the BET flow method (single point type). Measuring equipment: HM model-1208 (Mountech Co., Ltd.)

[0063] <Electron microscope> The sample powder was spread thinly on a dedicated stage, and the particle surface was uniformly coated with platinum-palladium. The sample powder was then stored in a measurement chamber, and irradiated with an electron beam at an accelerating voltage of 5 kV in a vacuum state, and the surface condition was observed by detecting the secondary electrons generated. In order to avoid biased observation results, observations were made in multiple fields of view at magnifications ranging from 50 to 3000 times. Measuring equipment: Scanning Electron Microscope S-3700N (Hitachi High-Technologies Corporation)

[0064] The D50 particle size, which means the average particle size, of psyllium A and B was 14.4 μm and 93.2 μm, respectively, with psyllium A having smaller particles. Furthermore, the results of observation under an electron microscope showed that psyllium A was composed of significantly smaller particles than psyllium B. The specific surface area was 1.55 m 3 / g and 0.19 m 3 / g, a difference of approximately 8 times was observed. As shown in Test Example 2 and Table 2, both psyllium A and B were confirmed to increase tablet hardness and improve moldability, but it was also revealed that among psyllium, psyllium with a small particle size and a large specific surface area was more effective in significantly improving tablet moldability.

[0065] Test example: Dissolution test of a composition containing polysaccharide and barium (4-1) Preparation of coated tablets containing polysaccharides and barium Approximately 670 mg (663.7 mg to 680.5 mg) of barium-containing tablets (plain tablets) containing psyllium and HPMC shown in Table 4 were prepared, and enteric-coated with shellac to produce enteric-coated solid oral compositions (coated tablets). Details are described below.

[0066] 150g of polysaccharide powder, 975g of barium, and 330g of crystalline cellulose were placed in a plastic bag, and the plastic bag was mixed by shaking it by hand mainly vertically for about 1 minute. The mixture was sieved to obtain a first mixed powder. 30g of silicon dioxide and 15g of calcium stearate were mixed in a plastic bag (mixed by shaking it vertically), sieved, and 90g of the first mixed powder was added thereto and mixed in the bag in the same manner to obtain a second mixed powder. The second mixed powder and the remaining first mixed powder were placed in a plastic bag and mixed in the same manner to obtain 1500g of powder for tableting. The total polysaccharide blending ratio was 10% by mass.

[0067] The powder was compressed into tablets using a rotary tablet press (punch: φ9.0 mm) with the scale settings for the main pressure and preload set at 1.4 and 3.0, respectively, to obtain tablets (plain tablets) containing polysaccharides and barium. The weight per tablet is shown in Table 4.

[0068] A mixture of 2000 g of aqueous shellac solution and 40 g of sucrose fatty acid ester was heated to 60°C to dissolve the solids, and then 40 g of D-sorbitol was added and dissolved to prepare a coating solution. 1 kg of plain tablets were placed in a coating machine, and the coating solution was sprayed on the tablets at an inlet air temperature of 80°C to obtain coated tablets (4-1) containing polysaccharides and barium. The amount of coating was 8% by mass based on the total mass of the solid oral composition.

[0069] (4-2) Preparation of uncoated tablets containing no polysaccharides but containing barium A barium-containing plain tablet (4-2) was obtained in the same manner as described in (4-1), except that HPMC and psyllium were not added and their weight was replaced with crystalline cellulose.

[0070] [Table 4]

[0071] (4-3) Manufacture of coated tablets containing polysaccharides and barium for use in dissolution tests In order to evaluate the dissolution property of the coated tablet (4-1), 30 g of a dye was added. In detail, the plain tablet (4-3) and the coated tablet (4-3) were produced in the same manner as described in (4-1), except that a part (30 g) of the crystalline cellulose was replaced with 30 g of a dye when preparing 1500 g of the powder for tableting to produce the coated tablet (4-1).

[0072] (4-4) Manufacture of coated tablets (control) containing no polysaccharides but containing barium for use in dissolution tests In order to evaluate the dissolution property of the coated tablet (4-2), 30 g of a dye was added. In detail, the plain tablet (4-4) and the coated tablet (4-4) were produced in the same manner as described in (4-2), except that a part (30 g) of the crystalline cellulose was replaced with 30 g of a dye when preparing 1500 g of the powder for tableting to produce the coated tablet (4-2).

[0073] (4-5) Dissolution test of uncoated tablets (measurement of 50% dissolution time) (intestinal sustained release) Dissolution tests were conducted on the plain tablets (4-3) and (4-4) to evaluate their sustained release properties. The details are described below.

[0074] A dissolution test was conducted according to the dissolution test method (paddle method) listed in the 17th edition of the Japanese Pharmacopoeia. 1000mL of the second dissolution test liquid was poured into a dedicated container, one test tablet was placed in, and the liquid was stirred with a paddle (stirring speed: 50 rpm). After the test tablet was placed in the second dissolution test liquid, 5mL of the liquid was sampled at the specified times (30, 60, 120, 180, 240, 300, 360, 420, 1380, 1440, 1920, 2820 minutes) and the absorbance (510nm) was measured with an absorption photometer. Three tablets were used for each sample in this test, and a graph (Figure 2) was created using the average value.

[0075] A graph was created by plotting the dissolution rate (%) at each predetermined time on the vertical axis and the time elapsed since the tablet was placed in the second liquid on the horizontal axis, and the time when the dissolution rate reached 50% (50% dissolution time) was derived from the graph. The graphs for the control tablet (●; tablet (4-4)) and the tablet containing polysaccharide and barium (■; tablet (4-3)) are shown in FIG. 2. From this graph, the 50% dissolution time was 60 minutes for the control tablet and 750 minutes for the tablet containing polysaccharide and barium. It was concluded that the difference in dissolution time was due to the presence or absence of polysaccharide in the formulation. The 50% dissolution time of the tablet containing polysaccharide and barium was 1250% (750 / 60) of that of the control tablet, confirming that the tablet had sufficient sustained release properties in the presence of intestinal fluid.

[0076] (4-6) Evaluation of acid resistance of coated tablets containing polysaccharides and barium A dissolution test was conducted to evaluate the barrier properties of the coated tablet (4-3) against gastric juice. The details are as follows.

[0077] One test tablet was placed in a container containing the first dissolution test fluid, and the fluid was stirred with a paddle. After the test tablet was placed in the first dissolution test fluid, 5 mL of the fluid was sampled at the specified times (30 minutes, 60 minutes, 120 minutes, and 180 minutes) and the absorbance (510 nm) was measured using an absorption photometer. Three tablets were used in this test, and the average value was calculated.

[0078] The graph (Figure 3) was created using the same procedure as for creating the graph (4-5). The coated tablet (coated tablet (4-3)) containing polysaccharides and barium did not dissolve for at least 3 hours in the first fluid of the dissolution test. This confirmed that the coated tablet containing polysaccharides does not dissolve in the stomach. From the intestinal sustained release of the plain tablet (4-3) confirmed in (4-5) and the acid resistance of the coated tablet (4-3) confirmed in this test, it was confirmed that the coated tablet containing polysaccharides can deliver the core components to the lower part of the digestive tract.

[0079] Test Example 5: Observation of the delivery of barium-containing tablets into the digestive tract using X-rays The coated tablet (4-1) containing polysaccharides and barium and the plain tablet (4-2) containing no polysaccharides but barium were administered to human subjects (n=2) as test tablets, and the degree of dissolution of the test tablets in the body was evaluated by observing X-ray images of the subjects' abdomen taken by a specialist doctor. Details are described below. The subjects took one test tablet on the morning of the day of measurement, and then X-rays of the abdomen were taken multiple times for up to 6 hours without eating. The subjects were fasted from 9 p.m. on the day before the measurement, and drank 180 ml of water when taking the test tablet. X-rays were irradiated 30, 90, 180, 240, 300, and 360 minutes after taking the test tablet, and photographs of the inside of the body were taken. The obtained X-ray images are shown in Figure 4 (subjects A and B who took plain tablet (4-2)) and Figure 5 (subjects C and D who took coated tablet (4-1)). The test tablet contains barium, so it appears white in the X-ray image.

[0080] Under the supervision of a doctor, the state of disintegration and delivery location of the test tablet were judged from the position of the test tablet that appeared white on the X-ray image. When the test tablet was clearly no longer in its original shape, it was judged to have completely disintegrated.

[0081] It was confirmed that the uncoated tablet (4-2) not containing polysaccharides had already disintegrated 90 minutes after ingestion (jejunum) (Figure 4). In contrast, the coated tablet (4-1) containing polysaccharides had not disintegrated even 360 minutes after ingestion and had reached the ileum (Figure 5). From these results, it was confirmed that when enteric coating is applied, if the uncoated tablet constituting the core has sustained release properties as shown by the dissolution test, the tablet can be delivered to the lower part of the digestive tract after the stomach (at least the ileum in the case of Figure 5) without significant disintegration. Therefore, the delivery site (jejunum, ileum, large intestine, etc.) can be adjusted by adjusting the HPMC or psyllium content in the coated tablet (4-1).

[0082] Test Example 6: Measurement of the bioavailability of vitamin C in vitamin C-containing coated tablets (6-1) Manufacturing of Vitamin C-containing Coated Tablets Approximately 350 mg tablets (plain tablets) containing psyllium and HPMC were prepared, and enteric-coated with a solution containing shellac to produce an enteric-coated solid oral composition, as described in detail below.

[0083] The four formulations shown in Table 5 were mixed as follows. The vitamin C content in each formulation was 200 mg / tablet. The vitamin C preparation, maltitol, crystalline cellulose, psyllium, and HPMC were placed in a plastic bag, and the plastic bag was shaken by hand mainly vertically for about 1 minute to mix. The mixture was sieved (using a No. 22 sieve) to obtain a first mixed powder. An appropriate amount of this first mixed powder was taken, and silicon dioxide and sucrose fatty acid ester, which had been sieved in advance, were added, and the mixture was mixed by shaking vertically using a plastic bag for about 1 minute. The entire amount of this powder was added to the first mixed powder and mixed in the same manner to obtain 1.5 kg of powder for tableting.

[0084] [Table 5]

[0085] The raw powder was compressed into tablets using a rotary tablet press (punch: φ9.5) with the main pressure and preload scales set to 1.85 and 4.0, respectively, to produce uncoated tablets (approximately 350 mg). The hardness of 10 uncoated tablets was measured with a hardness tester, and the uncoated tablets that were the basis for the coated tablets (6-1) to (6-4) had a hardness of 9.1 to 10.4 kgf / cm. 2 It was confirmed that the tablets had very little variation in hardness. Furthermore, coating for delivering these plain tablets to the small intestine was carried out as follows. A mixture of 1027 g of aqueous shellac solution and 20.5 g of sucrose fatty acid ester was heated to 60 ° C. to dissolve all the raw materials, and then 20.5 g of D-sorbitol was added and dissolved to prepare a first coating liquid. Separately, 49.84 g of HPMC was added to 200 g of hot water and mixed, and 462.16 g of water was added and dissolved to prepare a second coating liquid. The first coating liquid and the second coating liquid were mixed to prepare a coating liquid. 1 kg of plain tablets were fed to a coating machine, the inlet air temperature was set to 80 ° C., and the coating liquid was sprayed to obtain a coating agent. The coating amount was 7% by mass with respect to the total mass of the coated tablets for each coated tablet.

[0086] (6-2) Measurement of Vitamin C bioavailability A human test was conducted to measure the vitamin C utilization rate in the body for the coated tablets (6-1) to (6-4). Five tablets of each coated tablet were swallowed without chewing with 120 mL of water. The vitamin C intake for five tablets was 1,000 mg. After ingestion, urine was collected every two hours, and all urine up to the 18th hour was collected. The amount of urine collected was measured using a graduated cylinder, and the amount of vitamin C in urine was quantitatively measured using Kenis's ascorbic acid (vitamin C) test paper Quantofix. Since it is known that vitamin C is not easily metabolized in the liver and is excreted in urine unchanged, it was determined that the total amount of vitamin C in urine measured was not utilized in the body, and the amount obtained by subtracting the amount excreted in urine from the amount ingested (1,000 mg) and dividing the result by the amount ingested was used as the utilization rate in the body (see below). The results are shown in Figure 6. (Internal utilization rate calculation method) ((Total VC intake – Urinary VC) / Total VC intake) x 100 = Bioavailability (%) *VC stands for vitamin C (ascorbic acid).

[0087] When the coated tablet (6-1) not containing psyllium or HPMC was taken, the bioavailability of vitamin C was about 57%, but when the coated tablets (6-2) to (6-4) were taken, the bioavailability increased in proportion to the amount of psyllium and HPMC, reaching a maximum of 92% (coated tablet (6-4)). The improvement in bioavailability was thought to be due to the fact that the coated tablet exhibited sustained release properties in the small intestine due to the inclusion of psyllium and HPMC, so that VC was not released and absorbed in large amounts in the small intestine at once, but was released and absorbed gradually. This effect was first recognized in this experiment, but it was presumed that the same effect would be obtained not only for vitamin C, but also for water-soluble vitamins with similar properties (B1, B2, B6, B12, nicotinamide, pantothenic acid, etc.).

Claims

1. A solid oral composition having a core containing hydroxypropyl methylcellulose and psyllium having an average particle size of 1 μm to 70 μm, the core being coated with an enteric coating agent.

2. The composition according to claim 1, wherein the polysaccharide is contained in an amount of 1 to 90% by mass based on the total mass of the core.

3. The composition according to claim 1 or 2, containing psyllium in an amount of 0.4 to 30% by mass based on the total mass of the core.

4. The composition according to any one of claims 1 to 3, wherein the enteric coating agent comprises at least one selected from the group consisting of shellac, zein and sodium alginate.

5. The composition according to any one of claims 1 to 4, which is an intestinal sustained release preparation.

6. The composition according to any one of claims 1 to 5, which is for delivery to at least one site selected from the group consisting of the jejunum, the ileum, and the large intestine.

7. The composition according to any one of claims 1 to 6, which is for food use.

8. The composition according to any one of claims 1 to 7, wherein the core further contains a vitamin and is for improving vitamin absorption.

Citation Information

Patent Citations

  • Edible slow-releasing granule

    JP1986141862A

  • Laxative composition

    JP1991052819A

  • Coating material disintegrating in large intestine and drug capable of disintegration in large intestine

    JP1992368321A

  • Method for purifying water-soluble seed polysaccharides

    JP2003082003A

  • Sustained release formulation

    JP2007507491A